Rethinking resistance - Lim, CM (2020)
This thesis is a collection of four discrete essays on the topic of political resistance. While the contents of the individual essays are disparate, they are nonetheless connected by substantive and methodological themes. I discuss these issues, and the broader framing of the thesis, in the Introduction.